Premenstrual Syndrome Based On Physical Activity, Body Mass Index And Blood Pressure In Adolescent Girls - Nisa, Juhrotun; Hidayah, Seventina Nurul; Izzah, Nur Syifa Karomatul (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2023)
Background: One of the risk factors for PMS is physical activity, where during the COVID-19 pandemic there was a decrease in physical activity with PPKM. The impact of this decrease in physical activity is an increase in BMI. Obese women are more than twice as likely to have PMS, and obesity can also increase blood pressureObjective: to determine the relationship between physical activity, BMI and blood pressure with the incidence of PMS in adolescent girls.Method: This research is a cross sectional study. The population is young women in SMA N 1 Pagerbarang. With a total sample 212 people and the sampling technique uses quota sampling. Data collection by questionnaire and atropometric measurements of weight and height. Data analysis using chi square.Results and Discussion: A total of 45.8% of respondents experienced PMS. 46.7% had light physical activity, 54.7% had normal BMI and 87.3% had normal blood pressure 87.3%. Test the relationship between PMS with physical activity obtained P = 0.001, PMS with BMI with P = 0.005, and PMS with Blood Pressure with P value = 0.524.Conclusion: there is a relationship between physical activity and BMI with PMS, but there is no relationship between PMS with blood pressure. Keywords: PMS; Physical Activity; BMI; Blood Pressure.